Diet influences latitudinal gradients in life‐history traits, but not reproductive output, in ectotherms. Issue 12 (28th September 2021) - Bansal, Udita; Thaker, Maria
Abstract: Aim: Latitudinal gradients in life‐history traits are apparent in many taxa and are expected to be strong for ectotherms that have temperature‐driven constraints on performance and fitness. The strength of these gradients, however, should also be affected by diet. Because diet type (carnivory, omnivory, herbivory) influences accessibility to nutrition and assimilation efficiency, we aim to study how diet affects latitudinal gradients in lifetime reproductive output and the underlying life‐history traits in ectotherms. Location: Global. Time period: Recent. Major taxa studied: Lizards (Reptilia, Squamata, Sauria). Methods: We used empirical (352 species) and phylogenetically imputed data (563 species) to analyse the interactive effects of latitude and diet on life‐history traits (longevity, age at maturity, reproductive life span, hatchling mass, clutch/brood size, clutch/brood frequency, female mass) and lifetime reproductive output of lizards. Results: Lifetime reproductive output does not significantly differ in lizards across diet types, and only carnivores exhibit a small increase at higher latitudes. Diet type, however, influences latitudinal patterns of individual life‐history traits. Carnivores exhibit a shift towards 'slower‐paced' life histories at higher latitudes for most traits (increased longevity, age at maturity, reproductive life span, and decreased clutch frequency). By contrast, herbivores either display 'faster‐paced' life histories (reduction in reproductive life span, hatchling mass, female mass) or no change (clutch frequency, clutch size, age at maturity) at higher latitudes. Omnivores exhibit intermediate and muted latitudinal patterns. Main conclusions: We suggest that the nutritional challenges of herbivory, compounded by thermal constraints at higher latitudes, may explain differences in life‐history characteristics of herbivorous ectotherms. Intermediate patterns exhibited by omnivores highlight how flexibility in diet can buffer environmental challenges at higher latitudes. Our results indicate that lizards with different diet types display various trends in their life histories across latitudes, which eventually balance out to result in similar reproductive outputs throughout their lifetime, with little benefits to carnivory.